Employment Strategies in Applied Universities: A Case Study of Shanxi Technology And Business College in the New Era - gao, yanxia (Pacific International Journal, 2023)
The rapid expansion of higher education in China has led to a transformation in the employment landscape for college graduates. In response, the government has established a new employment market mechanism that poses challenges for employment guidance departments. The employment outcomes of college students are closely tied to the development and competitiveness of universities. To address these challenges, applied universities must enhance the comprehensive qualities and employability of their students through long-term planning and coordination. This paper examines the employment work in applied universities in the new era, focusing on the case of Shanxi Technology and Business College. The study highlights the requirements for effective employment strategies, including leadership involvement, coordination, and engagement of all staff members. It also discusses the employment statistics of the 2022 graduates from Shanxi Technology and Business College. The paper outlines the employment strategies employed by the college, such as employment guidance classes, improving the quality of employment education, and establishing on-campus and online recruitment platforms. It emphasizes the coordinated efforts and responsibilities of the college leadership, active participation from various departments, transformation of educational guidance, and the implementation of multiple measures for employment success. The college also emphasizes the accurate collection and statistical verification of graduates' employment data.This study provides insights into the employment work in applied universities, offering valuable strategies and practices for navigating the new era of college graduate employment.